Array Comparative Genomic Hybridization in Ulcerative Colitis Neoplasia: Single Non-Dysplastic Biopsies Distinguish Progressors from Non-Progressors - Bronner, Mary P. (2010)
Approximately 10% of ulcerative colitis patients develop colorectal neoplasia. At present, identification of this subset is markedly limited and necessitates lifelong colonoscopic surveillance for the entire ulcerative colitis population. Better risk markers are needed to focus surveillance onto the patients most likely to benefit. Using array-based comparative genomic hybridization, we analyzed single, non-dysplastic biopsies from three patient groups: ulcerative colitis progressors (n=9) with cancer or high-grade dysplasia at a mean distance of 18 cm from the analyzed site; ulcerative colitis nonprogressors (n=8) without dysplasia during long-term surveillance; and non-ulcerative colitis normal controls (n=2). Genomic DNA from fresh colonic epithelium purified from stroma was hybridized to 287 (low-density) and 4,342 (higher-density) feature bacterial artificial chromosome arrays. Sample-to-reference fluorescence ratios were calculated for individual chromosomal targets and globally across the genome. The low-density arrays yielded pronounced genomic gains and losses in 3 of 9 (33%) ulcerative colitis progressors but in none of the 10 control patients. Identical DNA samples analyzed on the higher density arrays, using a combination of global and individual high variance assessments, distinguished all 9 progressors from all 10 controls. These data confirm that genomic alterations in ulcerative colitis progressors are widespread, even involving single non-dysplastic biopsies far distant from neoplasia. They therefore show promise toward eliminating full colonoscopic surveillance with extensive biopsy sampling in the majority of ulcerative colitis patients.